A cross sectional study to assess the prevalence of microalbuminuria in patients with type 2 diabetes mellitus - I., Girish; S. B., Vijeth; H. V., Nandini (International Journal of Research in Medical Sciences, 2017)
Background: Microalbuminuria is an earliest marker of overt diabetic nephropathy, hence monitoring microalbuminuria in patients with diabetes mellites helps to predict and prevent overt diabetic nephropathy. This cross-sectional study was done to find out the prevalence of microalbuminuria in 200 patients with diabetes mellitus attending medicine OPD of Basaweshwara medical college hospital (BMCH), Chitradurga. Methods: 200 patients with Diabetes mellitus visiting the medicine OPD of BMCH, Chitradurga were considered for the study. Patients history and physical examination findings like duration of diabetes, hypertension, smoking and BMI were considered. Relevant blood investigations like fasting blood sugar, glycated haemoglobin (HbA1c), serum cholesterol and creatinine were done. Microalbuminuria was assessed using dipstick kits in an early morning urine samples. Results: The prevalence of normoalbuminuria was 71% and microalbuminuria was 29%. The prevalence of microalbuminuria increased with the increase in duration of diabetes. Conclusions: Prevalence of microalbuminuria among the patients with diabetes depends upon risk factors like blood pressure control, duration of diabetes, fasting blood sugar and HbA1c. Early identification of high risk patients and the subsequent initiation of renal and cardiovascular protective agents helps to reduce the burden of diabetic kidney disease.